The role of macrophages in interstitial lung diseases: Number 3 in the Series "Pathology for the clinician" Edited by Peter Dorfmüller and Alberto Cavazza. (19th July 2017) - Rossi, Giulio; Cavazza, Alberto; Spagnolo, Paolo; Bellafiore, Salvatore; Kuhn, Elisabetta; Carassai, Pierpaolo; Caramanico, Laura; Montanari, Gloria; Cappiello, Gaia; Andreani, Alessandro; Bono, Francesca; Nannini, Nazarena
The finding of collections of macrophages/histiocytes in lung biopsy and bronchoalveolar lavage is relatively common in routine practice. This morphological feature in itself is pathological, but the exact clinical significance and underlying disease should be evaluated together with clinical data, functional respiratory and laboratory tests and imaging studies. Morphological characteristics of macrophages and their distribution along the different pulmonary structures should be examined carefully by pathologists. Indeed, haemosiderin-laden macrophages are associated with smoking-related diseases when pigment is fine and distribution is bronchiolocentric, while alveolar haemorrhage or pneumoconiosis are the main concerns when pigment is chunky or coarse and the macrophages show an intra-alveolar or perilymphatic location, respectively. In the same way, pulmonary accumulation of macrophages with foamy cytoplasm is generally associated with pathologies leading to broncho-bronchiolar obstruction ( e.g. diffuse panbronchiolitis, hypersensitivity pneumonia or cryptogenic organising pneumonia) or alternatively to exogenous lipoid pneumonia, some drug toxicity ( e.g. amiodarone exposure or toxicity) and metabolic disorders ( e.g. type B Niemann–Pick disease). This pathology-based perspectives article is aimed at concisely describing the diagnostic possibilities when faced with collection of macrophages in lung biopsy and cytology. Morphology and localisation of macrophages in the lungs is helpful in the diagnosis of interstitial lung disease http://ow.ly/7bci30bBwmQ